73.0k views
5 votes
Which of the following is the correct factored form of the given equation?

4x 2 - 11x + 6 = 0

(2x + 3)(2x + 2) = 0
(2x - 3)(2x - 2) = 0
(4x - 3)(x - 2) = 0

User Kia Kaha
by
5.3k points

2 Answers

6 votes

Answer:

(4x - 3)(x - 2) = 0

That's your answer!!

User Chris Buckett
by
5.2k points
2 votes

Answer:

(4x - 3)(x-2) = 0

Explanation:

4x² - 11x + 6 = 0

To factorize this equation,

-11

4x6

These numbers are the key to the solution:

find two numbers whose sum is -11 and the product is + 24 (4 x 6)

So, the numbers are -3 and -8

4x² - 8x - 3x + 6 = 0

4x(x -2) - 3(x - 2) = 0

(4x - 3)(x-2) = 0

User Bruce P
by
5.8k points